Models of Polish Legal Education during World War II – the Swiss Example - Leraczyk, Izabela (PRAWO i WIĘŹ, 2025)
The history of the teaching of Polish law during World War II is a multifaceted and complex phenomenon. On the map of ‘wartime’ universities, the camps for interned soldiers of the 2nd Infantry Rifle Division became important centres. It was there that, in agreement with the University of Freiburg, as well as the University of Zurich, the opportunity to study law was created for Poles between the years 1940 and 1945. The aim of this text is to analyse the surviving curricula of the two centres and to indicate the differences that existed between them. This information is analysed in the context of the objectives that guided the organisers of legal studies for Polish soldiers with a view to showing their realisation of the project, as well as the evolution of the original intentions.